Social Semiotic Reading of Shalawat Badar: The Response of the Pesantren Community to Indonesian Politics - Akhmad Saehudin; Minatur Rokhim; Ahmad Hifni (Diwan : Jurnal Bahasa dan Sastra Arab, 2022)
Literary work is a product of a socio-political context and ideology that exist and develop within a particular society, and this applies to literary texts of religious genres, one of which is Shalawat Badr (the Shalawat Badrs). Drawing a theoretical framework from social semiotics, meaning making as a socio-cultural practice, this study analyzes the religious text of Shalawat Badr composed by KH Ali Manshur, a kiai (Muslim cleric) from Jember, East Java during the 1960s. Results of textual and contextual analysis of the Shalawat Badr text suggest that the author successfully blended this literary text of religious genre with the dynamics of political contexts of his time. This Shalawat Badr not only represents the author’s feelings and ideological orientations in searching for the ultimate meaning of life but also deliberate and purposeful engagement with the socio-political realities of his time. In particular, Shalawat Badr reflects the identity and medium of movement and resistance of the Pesantren (Islamic boarding schools) to the dynamics of national politics especially at the end of the Old Oder era. Additionally, the textual material of Shalawat Badr highlights the socio-policital contestation of the Indonesian society in the Old Order, especially the resistance of Islamic boarding schools to the Indonesian Communist Party (PKI) movement. Indeed, the meaning and attribution of Shalawat Badr continue to evolve with time, that is, from the political resistance and struggle of the Pesantren vis a vis the PKI to the practical electoral instrument of the Nahdhatul Ulama (NU) Party to becoming part of music business industry by Islamic music groups in the latest era. مستلخص العمل الأدبي هو نتاج سياق اجتماعي سياسي وأيديولوجيي ويتطور في مجتمع معين ، وهذا ينطبق على النصوص الأدبية ذات الأنواع الدينية ، ومن بينها صلوات بدر. تأخذ هذه الدراسة إطارًا نظريًا من السيميائية الاجتماعية، أي ممارسة اجتماعية ثقافية، وتحلل هذه الدراسة النص الديني لصلوات بدر من تأليف الكياهي علي منشور، وهو عالم من علماء جمبر، جاوة الشرقية خلال السنة الستينيات. تشير نتائج التحليل النصي والسياقي لنص صلوات بدر إلى أن المؤلف قد نجح في مزج هذا النص الأدبي من النوع الديني بديناميكيات السياقات السياسية في عصره. لا تمثل صلوات بدر فقط مشاعر المؤلف وتوجهاته الأيديولوجية في البحث عن المعنى الحقيقي للحياة ولكن أيضًا انخراطه المتعمد والهادف في الحقائق الاجتماعية والسياسية في عصره. وعلى وجه الخصوص ، تعكس صلوات بدر هوية ووسيلة حركة ومقاومة المعاهد الإسلامية لديناميكيات السياسة الوطنية خاصة في نهاية عهد النظام القديم (orde lama). بالإضافة إلى ذلك ، تسلط المادة النصية لصلوات بدر الضوء على التنافس الاجتماعي والسياسي للشعب الإندونيسي خلال عهد النظام القديم ، وخاصة مقاومة المعاهد الإسلامية لحركة الحزب الشيوعي الإندونيسي (PKI). ويستمر معنى وإسناد صلوات بدر في التطور بمرور الوقت ، أي من المقاومة السياسية ونضال المعاهد الإسلامية تجاه الحزب الشيوعي الإندونيسي إلى الأداة الانتخابية العملية لحزب نهضة العلماء (NU)، إلى أن تصبح جزءًا من صناعة الأعمال الموسيقية من قبل مجموعات الموسيقى الإسلامية في العصر الحديث. الكلمات المفتاحية : صلوات بدر؛ المعاهد الإسلامية؛ السياسية؛ السيميائية الاجتماعية